Assessment and Management of Insensible Fluid Loss in Nursing Practice - Bbakri, Boshra Hassan; Salihah Hussain M. Domayan; Daifallah Zaid Alotaibi; Abdullah Fahad Al-Sahli; Mohammed Ali M. Almutairi; Sahar Ahmad Albishi; Nada Nazeh Almustafa; Saffanah Abdulrahman Almutair; Maliha Ahmad Aqeel Tomahy; Eman Ali Mohammed; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Water constitutes about 60% of body weight and is vital for homeostasis, nutrient transport, and metabolic processes. Insensible fluid loss—water lost through skin, respiration, and minimal fecal excretion—accounts for 30–50% of daily water loss and is clinically significant, especially in perioperative and critical care settings. Aim: To explore the physiological basis, clinical implications, and management strategies for insensible fluid loss in nursing and interprofessional practice. Methods: A comprehensive review of fluid physiology, perioperative fluid management protocols, and evidence-based interventions was conducted, emphasizing the “4-2-1” rule for maintenance fluids and strategies for estimating insensible losses in high-risk patients. Results: Insensible losses range from 400–800 mL/day in healthy adults but increase markedly with fever, burns, hyperventilation, or mechanical ventilation. Failure to account for these losses can lead to hypovolemia, impaired perfusion, and delayed recovery. Crystalloids remain first-line for fluid replacement, while colloids are reserved for specific indications such as severe hypoalbuminemia or burns. Advanced monitoring tools, including POCUS and hemodynamic devices, enhance accuracy in fluid assessment. Conclusion: Effective management of insensible fluid loss requires proactive estimation, individualized fluid therapy, and interprofessional collaboration. Integrating bedside assessment, laboratory data, and dynamic monitoring ensures optimal fluid balance and patient outcomes.